THE MANY FACES OF FOLEY: A JOURNEY OF DISCOVERY AND INFLUENCE ON PROFESSIONAL WRESTLING - Nicks, Adam Michael (Dialogue, 5(3), 2018)
Though the academic community often looks down on professional wrestling, there are examples in which the medium allows for elaborate and complex storytelling rivaling other forms of literature. During the 1990s, due to the constant blurring of the lines between reality and fiction within the world of wrestling and the increasingly intelligent audience that consumed the product, performers were forced to adapt to a more realistic style integrating their actual life events and personality into their on-screen personas. One sports entertainer of note was Mick Foley, who crafted three splintered characters he portrayed amongst numerous promotions. Each had their own trajectory and were representative of separate aspects of his own psyche. Cactus Jack was a brutally violent version of Foley hungry to succeed by any means necessary, Mankind was a Gothic personification of Foley’s insecurities, and Dude Love was an out-of-date projection of an adolescent Foley’s ideal, confident hero. Throughout Foley’s career he pioneered a new style of sports entertainment, set a new precedent for character development, and redefined physical expectations for what a performer could be. Mick Foley has since gone on to become a New York Times bestselling author, an advocate for the charity RAINN, a spoken word performer, and a Santa Claus portrayer. Keywords: Mick Foley, Mankind, Cactus Jack, Dude Love, professional wrestling, World Wrestling Federation, World Wrestling Entertainment, Attitude Era, sports entertainment, personas
Keywords: Type of access: Open Access